The Birth, Growth, and Development of Pedagogical Content Knowledge (Pck) - Kasi, Yohanes Freadyanus; Widodo, Ari; Samsudin, Achmad; Riandi, Riandi; Sola, German Yohanes; Pao, Benisius (KnE Social Sciences, 2024)
Pedagogical Content Knowledge (PCK) is the basic skill that represents teacher professionalism and has proven useful for investigations in documenting knowledge that makes a good teacher. Teachers are one of the recognized intellectual actors having a knowledge base and set of skills developed during their teaching activities, to produce competent and highly competitive human resources in dealing with the currents of globalization, accompanied by increasingly sophisticated technological development. This research aims to see, historically, the birth of PCK and the growth and development of research on PCK. The method used is a documentary study by analyzing documents, both journals and books that discuss the results of PCK research. The analysis shows that when PCK research began to grow and develop, there were differences in the term PCK. There was a pattern of change in PCK research, a fundamental change in PCK knowledge by integrating technology into it (TPACK). It can be summarized that the future PCK research is directed to PCK improvement strategies for preservice and in-service teachers, as well as training teachers to be able to integrate technology in classroom learning (TPACK). Keywords: birth, growth, development, pedagogical content knowledge (PCK)